2014
DOI: 10.1111/j.1532-950x.2014.12242.x
|View full text |Cite
|
Sign up to set email alerts
|

Ex VivoEquine Medial Tibial Plateau Contact Pressure With an Intact Medial Femoral Condyle, With a Medial Femoral Condylar Defect, and After Placement of a Transcondylar Screw Through the Condylar Defect

Abstract: Stifle flexion increases force, contact area, and stress load on the medial tibial plateau and is most pronounced caudally. An MFC defect alters load on the medial tibial plateau, and a transcondylar screw may reverse some of those changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Two previous studies have measured contact pressure ex vivo on the proximal tibia under the equine medial meniscus, but they did not agree on the shape of the pressure maps. The present results are most similar to Bonilla et al, predicting substantial abaxial pressure in the middle of the meniscus that is increased when an MFC void is present. If the increase in stress is magnified when joint flexion is allowed, as was demonstrated ex vivo, this may provide a mechanism for meniscal damage in horses with MFC SBC.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Two previous studies have measured contact pressure ex vivo on the proximal tibia under the equine medial meniscus, but they did not agree on the shape of the pressure maps. The present results are most similar to Bonilla et al, predicting substantial abaxial pressure in the middle of the meniscus that is increased when an MFC void is present. If the increase in stress is magnified when joint flexion is allowed, as was demonstrated ex vivo, this may provide a mechanism for meniscal damage in horses with MFC SBC.…”
Section: Discussionmentioning
confidence: 91%
“…This increase in stress occurs in the meniscal body, a common location of injury (Figure ), and may be exacerbated when the loaded stifle is flexed . Two previous studies have measured contact pressure ex vivo on the proximal tibia under the equine medial meniscus, but they did not agree on the shape of the pressure maps. The present results are most similar to Bonilla et al, predicting substantial abaxial pressure in the middle of the meniscus that is increased when an MFC void is present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Bonilla et al . also reported that the centre of the equine tibial plateau, that has no meniscal tissue cover, sustained increased stress loads throughout stifle flexion and could contribute to fraying of the meniscal inner border or formation of meniscal body tears.…”
Section: Discussionmentioning
confidence: 97%
“…The change in equine meniscal conformation from a C-shape to an L-shape described by Fowlie et al [22] that arises during stifle flexion may place the meniscal inner border under tension and could explain the fraying frequently observed at this location in all 3 meniscal segments in the present study. Furthermore, Bonilla et al [23] also reported that the centre of the equine tibial plateau, that has no meniscal tissue cover, sustained increased stress loads throughout stifle flexion and could contribute to fraying of the meniscal inner border or formation of meniscal body tears.…”
Section: Discussionmentioning
confidence: 99%